Decoction of Yougui Wan combined with Wuzi Yanzong Wan ameliorates thin endometrium in a mouse model - Xiaohong Zhou; Jun Xiang; Aifang Su (Journal of Obstetrics and Gynaecology)
Background This study aimed to determine the effect and mechanism of the Decoction of Yougui Wan combined with Wuzi Yanzong Wan (DYWWYW), a traditional Chinese herbal formula, in a mouse model with thin endometrium induced by 95% ethanol.Methods Thin endometrium mice were treated with progynova (0.002 mg) as well as a low and high dose of DYWWYW (0.05 and 0.5 mL DYWWYW, respectively, diluted in 2 mL normal saline). Western blotting and qRT-PCR analyses were performed to determine the protein and mRNA expression levels, respectively, of integrin αγβ3 and leukaemia inhibitor factor (LIF) in uterus tissues. Serum oestradiol and progesterone concentrations were determined via ELISA. The remaining thin endometrium mice were mated with male mice, and the number of embryos implanted in the different groups was calculated.Results A high dose of DYWWYW effectively ameliorated the injury of endometrium caused by 95% ethanol. The levels of oestradiol, progesterone, αγβ3 and LIF in thin endometrium mice treated with a high dose of DYWWYW were also significantly elevated. Additionally, a high dose of DYWWYW remarkably increased the number of embryo implantations in mice with thin endometrium.Conclusion DYWWYW has improvement effects on thin endometrium by elevating the levels of endogenous oestradiol, progesterone, αγβ3, and LIF in a mouse model.